2005
DOI: 10.1177/10883576050200030301
|View full text |Cite
|
Sign up to set email alerts
|

Using a Modified Social Story to Decrease Disruptive Behavior of a Child With Autism

Abstract: Despite the popularity of Social StoriesTM as an intervention for disruptive behavior in children with autism, there have been few investigations on the effectiveness of Social Stories. Scattone, Wilczynski, EdWards, and Rabian (2002) found that Social Stories decreased challenging behaviors in children With autism, but they identified verbal prompts as a source of variability to be examined in future study. The current study examined the effects of a modified social story, with and without verbal prompts, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 16 publications
1
70
0
2
Order By: Relevance
“…These findings reinforce the studies by Crozier et al (2005) who used social stories which had been modified to reduce the disruptive behavior of autistic children. Thus, it shows that the social story intervention which have been modified indicates that behavior which can be reduced through CeSo is disruptive, negative and anti-social behavior.…”
Section: Discussion and Implications Of The Studysupporting
confidence: 80%
See 1 more Smart Citation
“…These findings reinforce the studies by Crozier et al (2005) who used social stories which had been modified to reduce the disruptive behavior of autistic children. Thus, it shows that the social story intervention which have been modified indicates that behavior which can be reduced through CeSo is disruptive, negative and anti-social behavior.…”
Section: Discussion and Implications Of The Studysupporting
confidence: 80%
“…However, Crozier et al (2005) in his study showed that the disruptive behavior of autistic children decreased after using social stories. The effects were studied using the help of verbal and nonverbal prompts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This approach has been examined by researchers and found to be effective in improving social understanding and social behaviour in children diagnosed with ASDs (Attwood, 2007). Studies on the effects of the Social Stories TM intervention reveal promising results 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 regarding increases or reductions in targeted behaviours (Crozier & Tincani, 2005;Delano & Snell, 2006;Sansosti & Powell-Smith, 2006). This intervention has grown in popularity as it provides visual structure and sequencing to teach social skills and reduce problem behaviour in a nonintrusive way (Olley, 2005).…”
mentioning
confidence: 99%
“…[11]. In many of these studies, SS has been used either as a sole intervention [11] or combined with other interventions, such as verbal and pictorial prompts, reinforcement of appropriate responses, robot-assisted programs [19], and various priming strategies [20].…”
Section: Social Story In the Presence Of Dogs: An Animal-assisted Ementioning
confidence: 99%